Takılar ışığında Urartu, Geç Hitit ve Yeni Assur arasındaki kültürel etkileşim - Şen Saribaş, Bilun (My University, 2025)
Takılar Işığında Urartu, Geç Hitit ve Yeni Assur Arasındaki Kültürel Etkileşim başlıklı tezimizde, Demir Çağı'nda Anadolu ile Mezopotamya'nın kesişim noktalarında yer alan Urartu, Yeni Assur ve Geç Hitit kültürleri arasındaki takı geleneğine dayalı benzerlikler ve farklılıklar incelenmiştir. Bu inceleme; yazıtlar, mezar buluntuları, adak levhaları, takı örnekleri ve kaya kabartmaları üzerindeki betimlemeler aracılığıyla gerçekleştirilmiştir. Birinci bölümde, söz konusu üç uygarlık arasındaki siyasi ilişkiler ele alınmış, bu ilişkilerin kültürel etkileşim üzerindeki yansımaları değerlendirilmiştir. İkinci bölümde, takıların kullanım alanları açıklanmış; ardından takı yapımında kullanılan malzemeler ele alınmış ve bu malzemelerin kökenleri ile kullanım biçimleri açısından kültürler arası etkileşim karşılaştırmalı olarak ortaya konmuştur. Üçüncü bölümde ise, takılar türlerine göre sınıflandırılarak incelenmiş; Urartu, Yeni Assur ve Geç Hitit takı gelenekleri arasındaki ortak ve özgün unsurlar değerlendirilmiştir. Bu çalışma ile Demir Çağı'nda söz konusu üç kültürün takı geleneği aracılığıyla birbirlerini nasıl etkilediklerini ve bu etkileşimin çevre kültürlerle ilişkili olarak nasıl şekillendiğini ortaya koymayı amaçladık.

In this thesis titled Under the Light of Jewelry: Cultural Interaction Among Urartu, Neo-Hittite, and Neo-Assyrian Civilizations we examine the similarities and differences in jewelry traditions among the Urartian, Neo-Assyrian, and Late Hittite cultures, which were located at the intersection of Anatolia and Mesopotamia during the Iron Age. This analysis is conducted through inscriptions, burial findings, votive plaques, jewelry artifacts, and depictions on rock reliefs. In the first chapter, the political relations among the three civilizations are examined, and the cultural reflections of these interactions are critically evaluated. The second chapter outlines the various contexts in which jewelry was used, followed by a detailed examination of the materials employed in jewelry-making. It further presents a comparative analysis of the origins and usage patterns of these materials, highlighting intercultural interactions. The third chapter classifies and analyzes jewelry according to types, evaluating the shared and distinctive elements among the jewelry traditions of Urartian, Neo-Assyrian, and Late Hittite cultures. This study aims to demonstrate how these three cultures influenced each other through their jewelry traditions and how such cultural interactions were shaped in relation to surrounding cultures during the Iron Age.
Keywords: Assyrians; Asurlar; Civilization; Culture; fibula; Geç Hitit; History; Hititler; Hittites; jewelry; Kültür; lapis lazuli; lapis lazuli Urartu; Late Hittite; madalyon; medallion; Neo-Assyrian; obsidian; obsidyen; takı; Tarih; Urartians; Urartu; Urartular; Uygarlık; Yeni Assur